The use of fluorescence correlation spectroscopy to characterize the molecular mobility of fluorescently labelled G protein-coupled receptors - Kilpatrick, Laura E.; Hill, Stephen J. (Portland Press, 2016)
The membranes of living cells have been shown to be highly organized into distinct microdomains, which has spatial and temporal consequences for the interaction of membrane bound receptors and their signalling partners as complexes. Fluorescence correlation spectroscopy (FCS) is a technique with single cell sensitivity that sheds light on the molecular dynamics of fluorescently labelled receptors, ligands or signalling complexes within small plasma membrane regions of living cells. This review provides an overview of the use of FCS to probe the real time quantification of the diffusion and concentration of G protein-coupled receptors (GPCRs), primarily to gain insights into ligand–receptor interactions and the molecular composition of signalling complexes. In addition we document the use of photon counting histogram (PCH) analysis to investigate how changes in molecular brightness (ε) can be a sensitive indicator of changes in molecular mass of fluorescently labelled moieties.